2018
DOI: 10.4103/ejgd.ejgd_95_18
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the mandibular arch after rapid maxillary expansion in children: A three-dimensional analysis using digital models

Abstract: Maxillary posterior crossbite is detectable in the deciduous dentition of nearly 20.81% of the child population. [1,2] This transverse discrepancy does not self-correct, whether it is functional or skeletal, unilateral, or bilateral. [3][4][5] Rapid maxillary expansion (RME) is indicated in patients with posterior crossbite to correct the transversal discrepancy between arches by opening the midpalatal suture and expanding the maxillary molars. [6] The effects of this procedure on the mandibular arch are not w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Ugolini et al (2016) (Ugolini et al, 2016) observed a beneficial effect on mandibular intermolar distance post-RME, indicating an adaptive response of the lower arch to maxillary arch changes . Conversely, Pacheco et al (2018) (Pacheco et al, 2018), found that RME, specifically with Haas-type appliances, does not significantly increase mandibular intermolar width or arch perimeter in growing patients.…”
Section: Discussionmentioning
confidence: 97%
“…Ugolini et al (2016) (Ugolini et al, 2016) observed a beneficial effect on mandibular intermolar distance post-RME, indicating an adaptive response of the lower arch to maxillary arch changes . Conversely, Pacheco et al (2018) (Pacheco et al, 2018), found that RME, specifically with Haas-type appliances, does not significantly increase mandibular intermolar width or arch perimeter in growing patients.…”
Section: Discussionmentioning
confidence: 97%